2017
DOI: 10.1016/j.scitotenv.2017.06.185
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of chlortetracycline using immobilized laccase on Polyacrylonitrile-biochar composite nanofibrous membrane

Abstract: The continuous release of antibiotic compounds through wastewater effluent into environment has raised concerns about their potential problems for different organisms. Enzymatic degradation with laccase is a green option for removal of pharmaceutical compounds from aqueous media. In this study, laccase was immobilized onto homemade Polyacrylonitrile-biochar composite nanofibrous membrane and the obtained biocatalyst was employed for removal of chlortetracycline, a widely used antibiotic, from aqueous media in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Many studies showed that the combined use of BCs with metal oxides/metal nanoparticles could achieve higher removal efficiency in removal of pharmaceutically active compounds (Table 3) (Shan et al 2016;Kim and Kan 2016;Taheran et al 2017). Zhou et al (2017) reported a novel iron and zinc co-doped sawdust BC (Fe/Zn biochar) and employed it to remove tetracycline (TET) from aqueous solution.…”
Section: Removal Of Pharmaceutically Active Compounds By Biochar-basementioning
confidence: 99%
“…Many studies showed that the combined use of BCs with metal oxides/metal nanoparticles could achieve higher removal efficiency in removal of pharmaceutically active compounds (Table 3) (Shan et al 2016;Kim and Kan 2016;Taheran et al 2017). Zhou et al (2017) reported a novel iron and zinc co-doped sawdust BC (Fe/Zn biochar) and employed it to remove tetracycline (TET) from aqueous solution.…”
Section: Removal Of Pharmaceutically Active Compounds By Biochar-basementioning
confidence: 99%
“…Taking advantage of the membrane, good separation for alcohol and water mixture was also achieved (Lan et al 2016(Lan et al , 2018. Other applications of biochar-based membrane include controlled-release fertilizer (Zhou et al 2015), and enhanced degradation of organic pollutants by Absorb a wide range of organic solvents and oils with excellent recyclability and selectivity Wu et al (2013b) attaching enzyme (Taheran et al 2017). However, scalable, efficient and topical production of biochar membranes with tunable properties is essential for industrial applications to be feasible.…”
Section: Biochar-based 2d Membranementioning
confidence: 99%
“…The pH of the solution may change the ionization state of the amino acids in the enzyme and affect its structure and activity, and even lead to its denaturation. 37,38 Hence, the activity proles of free laccase and laccase immobilized on MBC were investigated by performing activity assays at different pH values. As shown in Fig.…”
Section: Stability Of L-mbcmentioning
confidence: 99%